Glas-Konsth - Månsson, Peder; Hansson, Martin (Hikuin, 2010)
The Glas-Art of Peder Månsson Introduction by Martin Hansson Peder Månsson (ca 1465-1534) was a member of the Order of S:t Bridget in Vadstena. He was sent to Rome as an envoy for his monastery. In Rome he stayed for sixteen years. During this time studied almost every topic ha came about. As a result of his studies, he wrote several books on various subjects. His topics varied from how to raise children, farming, war, but also the art of making glass. Many of his many books are compilations of earlier authors, some of antique origin. His Glas-Art is unfortunately incomplete but seems to have been based on Italian writers. In contrast to many of the topics on which he wrote, the art of making glass was a craft of which could have had personal experience, since it seems that glassmaking of some sort was taking place at the monastery in Vadstena. In his Glas-Art Peder Månsson describes the making of glass in the sixteenth century, which makes it an invaluable source for the glass industry of its time. Peder Månsson’s Glass-Art is preserved in the Royal Library in Stockholm, in the library at Uppsala University, and at the library in Linköping.